Trust issues - Elizabeth McCullough Keenan; Wands, Greg ([New York] : Dutton, 2025)
After their estranged mother's suspicious death and their stepfather Perry's sudden disappearance with the family fortune, estranged siblings Hazel and Kagan, both suspects in the investigation, must put aside their differences to track down the cunning conman who destroyed their lives and stole their inheritance.
new book 2025 winter.
Keywords: Siblings -- Fiction; Mothers -- Death -- Fiction; Stepfathers -- Fiction; Missing persons -- Fiction; Novels; Thriller fiction